2013
DOI: 10.3168/jds.2013-6911
|View full text |Cite
|
Sign up to set email alerts
|

Environmental efficiency of alternative dairy systems: A productive efficiency approach

Abstract: Agriculture across the globe needs to produce "more with less." Productivity should be increased in a sustainable manner so that the environment is not further degraded, management practices are both socially acceptable and economically favorable, and future generations are not disadvantaged. The objective of this paper was to compare the environmental efficiency of 2 divergent strains of Holstein-Friesian cows across 2 contrasting dairy management systems (grazing and nongrazing) over multiple years and so ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 42 publications
(48 reference statements)
1
25
0
Order By: Relevance
“…unit of milk or land), choice of which may lead to radically different conclusions [64]; DEA rather aggregates farm impacts and outputs altogether , providing a single eco-efficiency measure for the whole farm. It is noteworthy, however, that two recent DEA studies found that intensification at cow-level actually resulted in better environmental performance at farm-level, regardless of feed self-sufficiency levels as reflected by two different feeding practices (lower versus higher reliance on imported concentrates) [13,19]. These findings demonstrate the potential for intensive farms to improve environmental performance [9], perhaps by adoption of highly self-sufficient management practices, in line with of agro-ecological concepts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…unit of milk or land), choice of which may lead to radically different conclusions [64]; DEA rather aggregates farm impacts and outputs altogether , providing a single eco-efficiency measure for the whole farm. It is noteworthy, however, that two recent DEA studies found that intensification at cow-level actually resulted in better environmental performance at farm-level, regardless of feed self-sufficiency levels as reflected by two different feeding practices (lower versus higher reliance on imported concentrates) [13,19]. These findings demonstrate the potential for intensive farms to improve environmental performance [9], perhaps by adoption of highly self-sufficient management practices, in line with of agro-ecological concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Yet eco-efficiency ratios have several drawbacks [10], for example the allocation of environmental impacts to several dairy farm products (milk, meat, crops) is challenging. Dairy studies are therefore increasingly coupling LCA indicators with the multiple-input, multiple-output method Data Envelopment Analysis (DEA [11]) to calculate single aggregated eco-efficiency scores per farm, by accounting for all LCA impacts (or carbon foot-printing indicators), inputs and outputs simultaneously [10,1219]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…March et al (2016) analysed the environmental efficiency of diverse milk production systems making use data from experimental dairy farms. Toma et al (2013) compared the environmental efficiency of two divergent strains of Holstein-Friesian cows across two contrasting dairy management systems. Picazo-Tadeo et al (2011) estimated the eco-efficiency scores at both farm and environmental pressure-specific levels for a sample of Spanish farmers operating in the rain-fed agricultural system of Campos County.…”
Section: Literature Reviewmentioning
confidence: 99%